Effective technical communications - Grumer, L.C.; Molinet, F. (IEEE circuits and devices magazine, 1997)
Effective technical communication is becoming more and more imperative in the success of just about any business enterprise, whether for-profit or not-for-profit, large or small, regardless of the industry or markets. Creating an impact is critical. In order to create that impact, the message must be carefully distilled for clarity, accuracy, and conciseness. This article applies to both written and oral presentations and explains how you can improve such technical communications within three contexts: situation, subject, and structure.